Analisis hubungan sumber informasi dengan pengetahuan komprehensif HIV pada wanita usia subur (WUS) - Ningtiyas, Rosalinda Syafira Cahya; Deniati, Ema Novita; Supriyadi, Supriyadi; Ulfah, Nurnaningsih Herya (Holistik Jurnal Kesehatan, 2025)
Background: Comprehensive knowledge of HIV among women of reproductive age is one of the key factors in preventing HIV transmission. Comprehensive knowledge of HIV is thought to be influenced by sources of information. Purpose: To analyze the relationship between information sources and comprehensive knowledge among women of reproductive age. Method: This study is a quantitative observational analytical study with a cross-sectional design, using data from the 2012 and 2017 Indonesian Demographic and Health Surveys, with a sample of 34,222 respondents in the 2012 Indonesian Demographic and Health Surveys data and 39,545 respondents in the 2017 Indonesian Demographic and Health Surveys data. The analysis was conducted uniaviately to describe the frequency, bivariately using the chi-square test, and multivariately using multiple logistic regression analysis to control for confounding variables and obtain odds ratio (OR) values. Results: In 2012, women of reproductive age who obtained information from one source were 1.86 times more likely to have incomplete knowledge (p<0.001), and those with no source of information were 1.92 times more likely (p=0.017). In 2017, the same results were found with a 1.74 times higher chance (p<0.001) for one source of information and a 2.02 times higher chance (p=0.046) for those without any source of information. Conclusion: Incomplete knowledge among women of reproductive age was significantly associated with fewer sources of information received, with consistent results in 2012 and 2017.   Keywords: Comprehensive Knowledge; HIV; Information Sources; Women of reproductive age.   Pendahuluan: Pengetahuan komprehensif HIV pada wanita usia subur (WUS) menjadi salah kunci utama pencegahan penularan HIV. Pengetahuan komprehensif HIV diduga dipengaruhi oleh sumber informasi. Tujuan: Untuk menganalisis hubungan sumber informasi dengan pengetahuan komprehensif HIV pada Wanita usia subur (WUS). Metode: Jenis penelitian ini adalah kuantitatif yang bersifat obervasional analitik dengan desain cross sectional menggunakan Data Survei Demografi dan Kesehatan Indonesia (SDKI) tahun 2012 dan 2017, dengan sampel sebanyak 34,222 responden pada data SDKI tahun 2012 dan 39,545 responden pada data SDKI tahun 2017. Analisis dilakukan secara univariat untuk memaparkan frekuensi, bivariat menggunakan uji Chi-square, dan multivariat menggunakan analisis regresi logistik berganda untuk mengontrol variabel perancu dan mendapatkan nilai odds ratio (OR). Hasil: Pada tahun 2012, WUS yang mendapatkan informasi dari satu sumber memiliki peluang 1.86 kali lebih tinggi untuk memiliki pengetahuan tidak komprehensif (p<0.001), dan yang tidak ada sumber informasi memiliki peluang 1.92 kali lebih tinggi (p=0.017). Pada tahun 2017, ditemukan hasil yang sama dengan peluang 1.74 kali lebih tinggi (p<0.001) pada satu sumber informasi dan 2.02 kali lebih tinggi  (p=0.046) pada yang tidak ada sumber informasi. Simpulan: Pengetahuan tidak komprehensif pada WUS secara signifikan berhubungan dengan semakin sedikitnya jumlah sumber informasi yang diterima, hasil tersebut konsisten pada tahun 2012 dan 2017.   Kata Kunci: Human Immunodeficiency Virus (HIV); Pengetahuan Komprehensif; Sumber Informasi; Wanita Usia Subur (WUS).